Increased Number of Human Cases of Influenza Virus A(H5N1) Infection, Egypt, 2014–15 - Samir Refaey; Eduardo Azziz-Baumgartner; Marwa Mohamed Amin; Manal Fahim; Katherine Roguski; Hanaa Abu Elsood Abd Elaziz; A. Danielle Iuliano; Noha Salah; Timothy M. Uyeki; Steven Lindstrom; Charles Todd Davis; Alaa Eid; et al. (Emerging Infectious Diseases, 2015)
During November 2014–April 2015, a total of 165 case-patients with influenza virus A(H5N1) infection, including 6 clusters and 51 deaths, were identified in Egypt. Among infected persons, 99% reported poultry exposure: 19% to ill poultry and 35% to dead poultry. Only 1 person reported wearing personal protective equipment while working with poultry.